Eﬀect of 12 weeks of selective cardiorespiratory endurance and plyometrics training on 800-meter rural collegiate athletes: a randomised controlled trial - Kumar, Neeraj (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
ntroduction. The 800-meter race is a middle-distance run where both anaerobic and aerobic energy systems contribute sig-niﬁcantly. The purpose of the present study was to determine the eﬀects of 12 weeks of selective plyometrics training in addition to their regular cardiorespiratory endurance training on the running performance in 800-meter rural collegiate athletes. Methods. A total of 110 healthy volunteer rural collegiate 800-meter athletes were randomly selected based on the inclusion and exclusion criteria. Participants were randomly allocated into two equal groups (group A and group B). Group A received only conventional training, including cardiorespiratory endurance training (CON), while group B received plyometric training combined with conventional training, including cardiorespiratory endurance training (PLYO). Statistical analyses used a one-way ANOVA with post hoc testing applied between all the parameters within the groups, and an unpaired t-test was used to compare post-training values between the CON and PLYO groups.Results. Group A’s mean age (years), weight (kg), height (cm), BMI (kg/m2), and pulse (beat/min) were 19.22 (1.53), 60.68 (10.47), 170.4 (6.55), 20.88 (3.48), and 83.78 (9.74), respectively, and group B’s were 19.48 (1.18), 63.16 (9.31), 171.8 (5.16), 21.37 (2.80), and 86.22 (11.69), respectively.Conclusions: The current study’s ﬁndings indicate that 12 weeks of selective plyometric training has a signiﬁcant impact in enhancing anaerobic power and a substantial eﬀect on improving the 800-meter running time of rural collegiate athletes, but had no impact on VO2 max.
Keywords: 800 m running; VO2 max; anaerobic power; F30; plyometrics